SOURCES OF GRAMMATICAL ERROR: A CASE STUDY ON INTRALINGUAL, INTERLINGUAL, CONTEXT OF LEARNING AND COMMUNICATION STRATEGIES FACTORS - WICAKSONO, AGUNG (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2014)
Abstract Everyone who learns a language produce errors. The errors occurring in the process of learning a foreign language should be considered as natural process. This study aims at  describing the sources of the grammatical errors made by the second year students of English Department at Faculty of Teaching Training and Education Nusantara PGRI University in writing subject focuses on using of expressing time and using past form. The closed ended questionnaire and structured interview were used to know the sources of cause of the error of the twenty four students.The result of the data analysis showed that  the highest sources of the errors  is interlingual transfer,there were 85% students, it means that the students were influenced much by the grammatical structure of native language (Indonesian) in making sentences. It is suggested that the English teachers not translated the part of the sentences one by one as it  caused the students get confused and make the errors. Key words: Grammatical Error, Intralingual, Interlingual, Communication Strategies.